Penerapan Terapi Deep Breathing Relaxation terhadap Penurunan Nyeri pada Ibu Post Operasi Sectio Caesaria - Rudi Karmi; Yosi Oktri; mega Diana (Ide Insan Kreatif, 2024)
Sectio cesarea is the act of making an incision to open abdominal wall and uterine wall to remove the fetus from the mother's womb. Postoperative sectio caesarea patients will feel pain due to an incision in the abdominal wall and uterus. The role of nursesare as nursing care providers in non-pharmacological pain management, one of them is relaxation techniques. Deep breathing relaxation is one of the non-pharmacological therapies that can be used to relax muscle tension so it can reduce the pain scale of postoperative mothers. Methods: This study used a case study of deep breathing relaxation therapy in post caesarea sectio operation mothers to reduce pain intensity. Results: The results of determiner case study can be concluded that the application of deep breathing relaxation therapy in postoperative sectio caesarea mothers is effective to accelerate the process of reducing the pain of post caesarea sectio operation mothers. Conclusions and suggestions: The application of deep breathing relaxation therapy to reduce pain has an effect so it can be applied by health workers as an effort to accelerate the process of reducing pain in post caesarea sectio operation mothers.Keywords: Deep Breathing, Sectio Caesarea, Pain